Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Pegawai di Hypermart Sampit dan Palangka Raya - Irawan Irawan; Vivy Kristinae (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2019)
The purpose of the study was to determine the effect of the work environment and compensation on job satisfaction which had an impact on the performance of employees in the Sampit and Palangka Raya Hypermart shopping center. The research sample of 150 workers was chosen based on a minimum work period of one year and analyzed by the quantitative method of SPSS 24.0. The results of the analysis prove that the work environment has a significant influence on job satisfaction while compensation is a variable that does not have a significant effect on job satisfaction. The work environment has a high impact on job satisfaction and job satisfaction has a significant influence on performance. The benefit of this research is to increase job satisfaction so that good performance impacts can improve service quality.